Traditional, Complementary, and Alternative Medicine in Nocturnal Enuresis in Children - Monireh Sadat Motaharifard; Masoumeh Mohkam (Mazandaran University of Medical Sciences, 2022)
Background: The use of complementary and alternative medicine (CAM) treatments in children is increasing. Due to the ineffectiveness of some pharmacological interventions or intolerance to their side effects, different types of CAM are used in various problems, such as enuresis in children. This study aimed to introduce the most common complementary and alternative medicine methods used for enuresis in the pediatric population. Objectives: This study aimed to introduce the most common complementary and alternative medicine methods used for enuresis in the pediatric population. Methods: Medical literature search was performed in several databases for a variety of Traditional, Complementary, and Alternative Medicine in nocturnal enuresis in children. Databases used were Google Scholar, Web of Science, Scopus, Cochrane Library, PubMed, and a number of Persian databases, including Magiran and SID. Clinical trials, case series, or case reports that had evaluated the effectiveness of these therapies in nocturnal enuresis in children were included. Data were collected in English or Persian from inception to early 2021. Results: Most studies had been performed on some CAM methods, such as acupuncture. In some methods, such as reflexology, the studies were limited to case reports and in others, such as aromatherapy, there was no study related to children's enuresis. Based on the results, most CAM methods have positive effects in the treatment of nocturnal enuresis and have their unique theories about the concepts of etiology, diagnosis, and treatment of disease. Conclusions: Despite the relatively high use of CAM treatments in nocturnal enuresis among children, evidence of their effectiveness is not enough. More clinical trials are required to evaluate the safety and efficacy of these methods.